Degradation-controllable plastic as well as preparation method and application thereof
By coating the enzyme in the metal frame material, a plastic that can be efficiently degraded in the natural environment is prepared, which solves the problems of low degradation efficiency and environmental pollution of existing plastics, and the negative correlation between degradation rate and thickness is achieved. And promotes crop growth.
Patent Information
- Application Number
- CN202411263271.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-10
- Publication Date
- 2024-12-13
AI Technical Summary
The existing plastics have low degradation efficiency under natural conditions, and the activity of biological enzymes in complex environments is difficult to maintain, resulting in increased environmental pollution and recycling difficulties.
Using polyester, enzymes with polyester degradation activity and metal frame materials (such as ZIF-8, NKMOF-101, ZPF-2 or ZIF-L), the enzyme is coated in the metal frame material and is uniformly dispersed or melted. Prepare degradable plastics, metal frame materials protect enzyme activity and controllable release to accelerate degradation.
It realizes efficient degradation of plastics under natural environment and compost conditions. The degradation rate is negatively correlated with thickness. After degradation, it promotes crop growth. It has excellent enzyme activity, solvent adaptability, acid resistance and antibacterial properties, reducing environmental pollution and recycling costs. .
Smart Images

Figure CN119119691A_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of degradable plastics, and more specifically to a degradable plastic and a preparation method and application thereof. Background Art
[0002] Under natural conditions, plastic decomposes very slowly, and direct incineration will further aggravate the greenhouse effect. Therefore, how to speed up the degradation of plastic under natural conditions is of great research significance.
[0003] Enzymes, as efficient catalysts, can selectively cut polymer chains under mild conditions and are a very potential way to degrade plastics.
[0004] Although bio-enzyme-catalyzed degradation of polyester plastics is a gentle, environmentally friendly and effective method, plastic classification requires a lot of manpower and material resources, and improper classification can easily cause plastics to contaminate each other, increasing the difficulty of plastic recycling. In addition, in a complex natural environment, it is difficult to maintain the activity of bio-enzymes, which leads to the obstruction of bio-enzyme degradation of plastics. Summary of the invention
[0005] The present invention provides a plastic with controllable degradation and a preparation method and application thereof, so as to solve the problems of low degradation efficiency and high environmental pollution of plastic in the prior art.
[0006] In a first aspect, the present invention provides a plastic with controllable degradation, comprising the following components: polyester, an enzyme with polyester degradation activity, and a metal frame material; wherein the enzyme with polyester degradation activity is coated in the metal frame material.
[0007] As a possible implementation, the enzyme having polyester degradation activity is one or a combination of lipase, protease, catalase and cutinase; and / or the metal framework material is selected from ZIF-8, NKMOF-101, ZPF-2 or ZIF-L.
[0008] In a second aspect, the present invention provides a method for preparing the plastic described in any possible implementation of the first aspect, comprising the following steps: mixing the polyester, the enzyme having polyester degradation activity and the metal frame material to form a uniform dispersion system to obtain the degradation-controllable plastic.
[0009] As a possible implementation method, the polyester, the enzyme having polyester degradation activity and the metal frame material are dissolved in an organic solvent; molded; and the degradation-controllable plastic is obtained.
[0010] As a possible implementation manner, the forming is to completely volatilize the solvent, or perform an electrospinning operation; and / or, the organic solvent is one or a combination of toluene, dichloromethane, N,N-dimethylformamide, acetone and tetrahydrofuran.
[0011] As a possible implementation method, the polyester, the enzyme having polyester degradation activity and the metal frame material are melted at 100-250° C. and molded to obtain the degradation-controllable plastic.
[0012] As a possible implementation manner, the forming is to perform a 3D printing operation.
[0013] In a third aspect, the present invention provides an application of the plastic described in any possible implementation of the first aspect or the plastic prepared by the preparation method described in any possible implementation of the second aspect in the preparation of plastics.
[0014] As a possible implementation manner, the plastic is used to prepare ground film.
[0015] As a possible implementation, the plastic is used to prepare packaging bags.
[0016] The plastic provided by the present invention accelerates the degradation of traditional polyester and polyamide plastics in natural environments (such as seawater) and under composting conditions, as well as the degradation of mulch in farmland in the form of additives. The metal frame material included in the raw materials for preparing the plastic provided by the present invention can effectively protect the enzyme and avoid the loss of enzyme activity; the metal frame material is responsive and can controllably release the enzyme, further making the degradation of the plastic controllable.
[0017] The plastic provided by the present invention has excellent enzyme activity, plastic degradation activity, solvent adaptability, molding method adaptability, acid resistance, water stability, biocompatibility, antibacterial properties, high degradation efficiency, and a negative correlation between the degradation rate and the thickness of the plastic. In addition, the plastic provided by the present invention has a certain effect of promoting crop growth after degradation.
[0018] The plastic provided by the invention solves the problems of long degradation period, harsh degradation conditions and high degradation cost of current polyester plastic. BRIEF DESCRIPTION OF THE DRAWINGS
[0019] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0020] Figure 1The enzyme activity test of lipases from different sources provided in the embodiments of the present invention in different pH buffer solutions and different temperatures, wherein lipase 1 is derived from Pseudomonas cepacia, lipase 2 is derived from porcine pancreas, lipase 3 is derived from Candida antarctica, and lipase 4 is derived from Aspergillus niger.
[0021] Figure 2 TEM images of different MOF materials provided in embodiments of the present invention before and after treatment in water and acidic buffer.
[0022] Figure 3 The PXRD patterns of the MOF material provided in the embodiment of the present invention before and after treatment in water and acidic buffer.
[0023] Figure 4 The analysis result diagram of the ZIF-L material and the lipase@ZIF-L material provided in the embodiments of the present invention, wherein A is a PXRD diagram, B is an FTIR diagram, and C and D are CLSM diagrams of the ZIF-L material and the lipase@ZIF-L material, respectively.
[0024] Figure 5 The effect of the lipase loading amount on the activity of the lipase@ZIF-L material provided in the embodiment of the present invention, wherein the left figure shows the change of loading amount with initial concentration, and the right figure shows the change of enzyme activity with time at different initial addition concentrations.
[0025] Figure 6 The stability of the lipase@ZIF-material provided in the embodiments of the present invention in different organic solvents, wherein the left figure is a mass change diagram of the lipase@ZIF-L material before and after immersion in an organic solvent, and the right figure is a PXRD diagram of the lipase@ZIF-L material before and after immersion in an organic solvent.
[0026] Figure 7 This is a graph showing the analysis results of the lipase@ZIF-L catalyst provided in an embodiment of the present invention before and after being embedded in the PCL membrane, wherein A is the PXRD graph, B is the TGA graph, and C and D are the CLSM graphs of PCL and PCL-Lipase@ZIF-L-PS, respectively.
[0027] Figure 8 This is a mass change curve of the degradation of PCL membrane by equal amounts of lipase and lipase@ZIF-L catalyst provided in an embodiment of the present invention, wherein the horizontal axis is time and the vertical axis is mass.
[0028] Fig. 9 This is a physical picture of the degradation of PCL membrane by equal amounts of lipase and lipase@ZIF-L catalyst provided in the examples of the present invention at different time points.
[0029] Fig.10The degradation degree of lipase@ZIF-L provided in the embodiment of the present invention after being embedded in the PCL membrane in different solvents.
[0030] Fig.11 The degradation degree of lipase@ZIF-L provided in the embodiment of the present invention after being embedded in the PCL membrane under different methods.
[0031] Fig.12 The effects of PCL film thickness and buffer volume on the degradation degree of PCL film by equal amounts of lipase and lipase@ZIF-L catalyst provided in the embodiments of the present invention, wherein the upper figure shows the effect of PCL film thickness on the degradation degree, and the lower figure shows the effect of solution volume on the degradation degree, and from left to right in the lower figure are 30mL, 300mL and 900mL respectively.
[0032] Fig.13 This is a curve showing the mass change of the lipase@ZIF-L catalyst embedded in the PCL membrane in water over time provided by an embodiment of the present invention.
[0033] Fig.14 This is the cell compatibility of the lipase@ZIF-L catalyst provided in the embodiment of the present invention after being embedded in the PCL membrane.
[0034] Fig.15 Two antibacterial tests of the lipase@ZIF-L provided in the embodiments of the present invention before and after it is embedded in the PCL membrane.
[0035] Fig.16 Actual pictures of the degradation of the PCL membrane embedded with the lipase@ZIF-L catalyst provided in the embodiments of the present invention in three kinds of soils, wherein the first row shows the degradation of the PCL-Lipase@ZIF-L-PS membrane in the soil, and the second row shows the degradation of the PCL membrane in the soil; the first column shows the corresponding membrane that is not mixed with the soil.
[0036] Fig.17 The degradation degree of the lipase@ZIF-L catalyst provided in the embodiment of the present invention embedded in the PCL film after seven days of reaction in three kinds of soil.
[0037] Fig.18 This is the effect of the lipase@ZIF-L catalyst provided in an embodiment of the present invention embedded in the PCL membrane and degraded on the growth of corn, wherein the left figure shows the growth status of corn, and the right figure shows the height calculation results of the roots, stems, leaves and total height. DETAILED DESCRIPTION
[0038] The following will be combined with the drawings in the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0039] All numerical values specified in the present invention (such as temperature, time, concentration and weight, etc., including the range of each thereof) can generally be appropriately changed by (+) or (-) approximate values in increments of 0.1 or 1.0. All numerical values specified can be understood as being preceded by the term "about". Degradation degree = mass of plastic reacted / initial mass of plastic, wherein the mass is obtained by weighing with a high-precision balance.
[0040] In order to solve the problems of low plastic degradation efficiency and high environmental pollution in the prior art, the embodiments of the present invention provide a plastic with controllable degradation and a preparation method and application thereof.
[0041] The plastic provided by the present invention accelerates the degradation of traditional polyester and polyamide plastics in natural environments (such as seawater) and under composting conditions, and accelerates the degradation of mulch in farmland in the form of additives. The metal frame material included in the raw materials for preparing the plastic provided by the present invention can effectively protect the enzyme and avoid the loss of enzyme activity; the metal frame material is responsive and can controllably release the enzyme, further making the degradation of the plastic controllable.
[0042] Furthermore, the present invention embodiment conducted a preparation experiment and performance test experiment of a controllable degradation plastic. It was verified that the plastic has excellent enzyme activity, plastic degradation activity, solvent adaptability, preparation method adaptability, acid resistance, water stability, biocompatibility, antibacterial properties, and has high degradation efficiency. The degradation rate is negatively correlated with the thickness of the plastic. It was also verified that the plastic provided by the present invention has a certain effect of promoting crop growth after degradation.
[0043] The technical solution of the present invention will be further described below in conjunction with specific embodiments.
[0044] Example 1
[0045] This example provides performance testing experiments of enzymes and MOF materials.
[0046] 2900 μL of phosphate buffer (50 mM, pH = 5.9-6.8) was added to the cuvette, 100 μL of 1 mg / mL different lipase solutions were added to the cuvette respectively, and then 30 μL of 100 mM 4-nitrophenyl acetate acetonitrile solution was added to the cuvette, and the absorbance value change at 402 nm was detected in real time using a UV-visible spectrophotometer to obtain the following: Figure 1The test results shown are Figure 1 It can be seen that the optimum pH of lipase is 6.8, the optimum temperature is 40-55°C, and lipase 1 has the best activity.
[0047] Four MOF materials (ZIF-8, NKMOF-101, ZPF-2 and ZIF-L) were placed in water and aqueous buffer solution with pH = 6.8 for 6 h, and the X-ray powder diffraction (PXRD) and transmission electron microscopy (TEM) changes of the materials before and after the reaction were tested. Figures 2-3 The results shown by Figures 2-3 It can be seen that the four materials did not decompose in water, but decomposed in buffer solution, and all four materials were pH responsive.
[0048] Example 2
[0049] This example provides a preparation experiment and performance testing experiment of lipase@ZIF-L.
[0050] In this example, enzyme@metal framework materials and PCL-enzyme@metal framework materials were prepared and their performance was tested. In this example, lipase@ZIF-L and PCL-lipase@ZIF-L were used as examples for illustration.
[0051] Lipase@ZIF-L was characterized by PXRD, infrared (FT-IR), and laser confocal (Confocal), and the following results were obtained: Figure 4 The results shown in Figure 2 and Figure 3 support each other’s characterization results, indicating that lipase@ZIF-L was successfully constructed.
[0052] By controlling the concentration of lipase in the reaction system, the loading amount of lipase in the lipase@ZIF-L composite catalyst was adjusted to obtain Figure 5 The results shown. Figure 5 It can be seen that the activity of the composite material is optimal when the enzyme concentration increases from 2 mg / mL to 8 mg / mL, the loading amount increases from 0.06 g / g to 0.18 g / g, and when the enzyme addition amount is 6 mg / mL.
[0053] The organic solvent stability of lipase@ZIF-L was tested by immersing it in different organic solvents (toluene, acetone, tetrahydrofuran, dichloromethane and chloroform) for 6 h. The quality and PXRD patterns of lipase@ZIF-L before and after immersion were tested. Figure 6 From the results shown, it can be seen that lipase@ZIF-L has good solvent stability.
[0054] The PXRD and thermogravimetric (TGA) characterizations of the PCL membrane and the PCL membrane embedded with lipase@ZIF-L catalyst, as well as the laser confocal microscopy characterization of the PCL membrane embedded with lipase@ZIF-L catalyst, were as follows: Figure 7 Results shown. Figure 7 The various characterization results in the paper support each other and together indicate that the lipase@ZIF-L catalyst is successfully embedded in the PCL membrane.
[0055] 100 mg of PCL membrane was placed in 30 mL of phosphate buffer (50 mM, pH = 6.8) for hydrolysis reaction at 40 °C for 3 days. The mass change of PCL membrane under different degradation time was tested, and the following results were obtained: Figure 8 and Fig. 9 The results are shown. Figure 8 and Fig. 9 It can be seen that, under the same amount of lipase added, embedding the lipase@ZIF-L composite catalyst into the PCL membrane can promote the degradation of the PCL membrane.
[0056] Without changing the amount of enzyme added and the total mass of the PCL membrane, the degradation degree of 100 mg of PCL membrane embedded with lipase@ZIF-L catalyst prepared in different solvents after hydrolysis for 3 days was studied. Fig.10 The results are shown. Fig.10 It can be seen that the hydrolysis of PCL membrane embedded with lipase@ZIF-L composite catalyst is not affected by the solvent.
[0057] Without changing the amount of enzyme added and the total mass of the PCL membrane, the degradation degree of 100 mg PCL membrane embedded with lipase@ZIF-L catalyst prepared by different methods after hydrolysis for 3 days was studied, among which, solvent evaporation: polyester, lipase and ZIF-L were dissolved in an organic solvent and the solvent was completely evaporated; heating and melting: polyester and lipase@ZIF-L were melted at high temperature and naturally cooled; 3D printing: polyester, lipase and ZIF-L were melted at high temperature and extruded using a 3D printer. Fig.11 The results are shown. Fig.11 It can be seen that the hydrolysis of PCL membrane embedded with lipase@ZIF-L composite catalyst is not limited by the method.
[0058] Without changing the amount of enzyme added and the total mass of PCL membrane, the degradation degree of 100 mg PCL membrane and PCL membrane embedded with lipase@ZIF-L catalyst at different diameters after hydrolysis in equal amount of phosphate buffer (50 mM, pH = 6.8) for 3 days was studied. The results are as follows Fig.12 As shown in the figure above, it can be seen that the degradation of PCL membrane is thickness-dependent. The thicker the thickness, the lower the degree of degradation. However, the thickness has no significant effect on the degradation of PCL membrane embedded with lipase@ZIF-L composite catalyst.
[0059] Without changing the amount of enzyme added and the total mass of PCL membrane, the degradation degree of 100 mg PCL membrane and PCL membrane embedded with lipase@ZIF-L catalyst was studied after hydrolysis in 30 mL, 300 mL and 900 mL of phosphate buffer (50 mM, pH = 6.8) for 3 days. The results are as follows Fig.12 As shown in the figure below, the degradation of PCL membrane showed volume dependence of phosphate buffer, while the degradation of PCL membrane embedded with lipase@ZIF-L composite catalyst was not affected.
[0060] 100 mg of PCL membrane embedded with lipase@ZIF-L catalyst was placed in 30 mL of aqueous solution and hydrolyzed at 40 °C for 3 days. The mass change of the membrane at different hydrolysis times was recorded, and the following results were obtained: Fig.13 The results shown in Figure 2 show that the PCL membrane embedded with lipase@ZIF-L catalyst has good water stability.
[0061] 3T3 cells were cultured in DMEM medium supplemented with 10% heat-inactivated fetal bovine serum (FBS; PAN) and 1% antibiotics (penicillin-streptomycin) in an incubator with 5% CO2 at 37°C. The cytotoxicity of MOFs was determined by 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT; Beyotime). Cells were seeded in 24-well plates at the desired density and cultured overnight. Membranes from different sources (food packaging, PCL membrane, PCL-Lipase@ZIF-L-PS membrane, supermarket packaging, pharmacy packaging, commercial antimicrobial membrane, and garbage bags) were cut into 1 cm 2 The cells were placed in the corresponding wells for culture and a blank control group was set up. After 6 hours, the membrane was removed and each well was washed with PBS. MTT solution (25 μL; 5 mg / mL) and 475 μL of culture medium were added to each well and incubated in the culture medium for 4 hours. The culture medium was removed and 500 μL of dimethyl sulfoxide (Sigma) was added to each well. The plate was read at λ = 490 nm. Among them, the cell survival rate was calculated as follows The results are as follows Fig.14 As shown, it can be seen that the PCL membrane embedded with lipase@ZIF-L catalyst has good biocompatibility.
[0062] In order to study the antibacterial activity of the material, Gram-negative Escherichia coli (E. coli) and Gram-positive Staphylococcus aureus (S. aureus) were selected for antibacterial tests. Before the antibacterial test, the culture dish and culture medium were sterilized by high pressure. The culture was placed in Luria-Bertani (LB) medium and cultured at 37°C and 200rpm / min with shaking. The bacterial suspension was added dropwise to the surface of PCL and PCL embedded with lipase@ZIF-L, respectively. Then, both were irradiated with simulated sunlight for 30 minutes and then thoroughly washed with saline. Finally, 30μL of the eluate was evenly spread on the LB agar plate, cultured in a 37°C incubator for 12 hours, and then the number of colonies was counted. Under the same conditions as above, the same experiment was carried out in the dark, and the results are as follows. Fig.15 As shown, PCL embedded with lipase@ZIF-L has excellent antibacterial effect.
[0063] 100 mg PCL membrane and PCL membrane embedded with lipase@ZIF-L catalyst were placed in 100 g soil from three different sources (water content 30% to 40%) and hydrolyzed at 40 °C for one week. 15 mL of water was added every 24 h to ensure the humidity of the soil. The physical pictures and degradation degree of PCL membrane and PCL membrane embedded with lipase@ZIF-L catalyst before and after hydrolysis were recorded, as shown in Figure 2. Fig.16 and 17 As shown, the degradation degree of PCL membrane embedded with lipase@ZIF-L catalyst is much higher than that of PCL membrane, which can achieve more than 90% degradation within one week.
[0064] The PCL membrane embedded with lipase@ZIF-L catalyst was placed in soil at a dosage of 100 mg / kg for degradation. 5 kg of soil containing PCL membrane degradation products and soil without degradation products were weighed for testing. Corn seeds were sown in the soil and cultivated for two weeks. The length of the root, stem and leaf of each group of corn seedlings was recorded. The results are as follows: Fig.18 As shown, it can be seen that the soil containing PCL film degradation products has a promoting effect on the growth of corn seedlings, because a small amount of zinc ions can promote the production of plant auxin.
[0065] Although the preferred embodiments of the present invention have been described, those skilled in the art may make other changes and modifications to these embodiments once they have learned the basic creative concept. Therefore, the appended claims are intended to be interpreted as including the preferred embodiments and all changes and modifications that fall within the scope of the present invention.
[0066] Obviously, those skilled in the art can make various changes and modifications to the present invention without departing from the spirit and scope of the present invention. Thus, if these modifications and variations of the present invention fall within the scope of the claims of the present invention and their equivalents, the present invention is also intended to include these modifications and variations.
Claims
1. A plastic with controlled degradation, characterized in that: The invention comprises the following components: polyester, enzyme with polyester degradation activity and metal frame material; Wherein, the enzyme having polyester degradation activity is coated in the metal frame material.
2. The plastic according to claim 1, characterized in that The enzyme having polyester degradation activity is one or a combination of lipase, protease, catalase and cutinase; And / or, the metal framework material is selected from ZIF-8, NKMOF-101, ZPF-2 or ZIF-L.
3. A method for preparing the plastic according to any one of claims 1 to 2, characterized in that: The method comprises the following steps: mixing the polyester, the enzyme with polyester degradation activity and the metal frame material to form a uniform dispersion system to obtain the degradation-controllable plastic.
4. The method according to claim 3, characterized in that The polyester, the enzyme with polyester degradation activity and the metal frame material are dissolved in an organic solvent; molded; and the degradation-controllable plastic is obtained.
5. The method according to claim 4, characterized in that The forming is to completely evaporate the solvent or perform electrospinning; And / or, the organic solvent is one or a combination of toluene, dichloromethane, N,N-dimethylformamide, acetone and tetrahydrofuran.
6. The method according to claim 3, characterized in that The polyester, the enzyme with polyester degradation activity and the metal frame material are melted at 100-250° C. and molded to obtain the controllable degradation plastic.
7. The method according to claim 6, characterized in that The forming is to perform a 3D printing operation.
8. Use of the plastic according to any one of claims 1 to 2 or the plastic prepared by the preparation method according to any one of claims 3 to 7 in the preparation of plastic products.
9. The use according to claim 8, characterized in that: The plastic is used for preparing ground film.
10. The use according to claim 9, characterized in that: The plastic is used for preparing packaging bags.
